Digital Literacy Based on Christian Education as a Formation Tool Characteristics of Lentera Harapan Middle School and High School Students in Kupang-NTT - Nenosaban, Sakheus Junias; Tari, Ezra (Kirana Publisher (KNPub), 2023)
The development of the world of education and the high use of digital media today, makes students and educators need to improve themselves in a better and positive direction. If, the use of media is not accompanied by good digital literacy. As a result, students are trapped in hoaxes, sexual exploitation, cyberbullying, hate speech, digital-based radicalism, thus degrading student morals and psychology. The purpose of this writing is to overcome the explosion of technological information that continues to increase in digital sources. As a student, you need to equip yourself in digital literacy to fulfill your responsibilities in the learning system. The presence of Christian Religious Education is to equip students to maintain Christian values in the learning process. The research method used is a literature study approach, and the results of research on educators/teachers and students of Lentera Harapan Middle School and High School Students Kupang-NTT. Through the Construction Tools of school digital literacy, it provides convenience and character development for students. digital literacy as an educational coaching tool to build the character of students or students who are critical and applicable, so as to have an impact on changes in character and social situations.